Dual Mobility Cups: An Effective Prosthesis in Revision Total Hip Arthroplasties for Preventing Dislocations. Issue 1 (January 2016) - Jauregui, Julio J.; Pierce, Todd P.; Elmallah, Randa K.; Cherian, Jeffrey J.; Delanois, Ronald E.; Mont, Michael A.
Purpose: Postoperative dislocation is one of the most common complications following total hip arthroplasty (THA), and dual mobility articulations have been designed to provide greater hip stability. However, there are few studies that have assessed outcomes of these designs in revision THAs. Our purpose was to evaluate differences in dislocation rates, aseptic survivorship, and patient outcomes between dual mobility articulations and conventional arthroplasties in the revision setting. Methods: Patients who underwent revision THA with dual mobility articulations (n = 60) were matched (1:2) to patients who had conventional single articulation prostheses (n = 120). They were matched for body mass index, age, gender, and Paprosky acetabular defect classification, and were followed up for a mean of 30 months (range, 18 to 52 months). The outcomes were evaluated preoperatively and at final follow-up using Harris Hip Scores, the University of California Los Angeles activity scale, and the Short Form-36 questionnaires. Results: The dual mobility group had lower dislocation (1.7% (1 out of 60) versus 5.8% (7 out of 120)) and aseptic loosening rates (1.7% (1 out of 60) versus 4.2% (5 out of 120)) compared to the control group. There were no significant differences in functional outcomes, activity level, or overall physical and mental health status between the 2 cohorts. Conclusions: When used in the revision setting, dual mobility bearings had fewer dislocations. We believe that these designs may lead to clinically significant improvements in complications while also improving patient reported and functional outcomes, but larger cohort studies are necessary for evaluation.